Evaluación de indicadores de producción de toros cruzados cebados en el Departamento de Arauca, Colombia (2014)
With the purpose of measuring production yields at a meat production farm, technical records for 597 crossbred Zebu steers fattened were examined in the period from 2006 to 2009 in municipality of Tame, in the department of Arauca, Colombia. Indicators of average daily gain (ADG), efficiency of production (EP), meat yield (R), meat yield per year (kg / animal / year) and of meat yield per hectare per year (kg / ha / year) were calculated. The data was analyzed using descriptive statistics. Year 2009 showed the best performance for GDP and kg / day / year yield was shown in year 2009 with 905 g and 330.3 kg and the lowest R 70.2% R, however, it was offset by efficiency production of meat / animal / year (365,5 kg). Meat production per area with 375 kg / ha / year excelled in 2007. The EP showed similar production for all years. It is concluded that in each period there is a wide variation in production due to initial weight and environmental conditions of each year. © 2014,Instituto Nacional de Investigaciones Agricolas (INIA). All rights reserved.